The Role of Pancasila in Building National Character Among Students - Adellia, Dinda (International Journal of Students Education, 2024)
Pancasila, as ideology and foundation of the Indonesian state, has significant role in formation character nation, especially among students who are generation successor. Pancasila as the foundation of the Indonesian state has five principles which reflect fundamental moral values. Through Pancasila education, students introduced to the values like justice social, unity, democracy, and just and civilized humanity. This helps to form strong moral foundation for generation young. Introduction ethics and morals. Current globalization and development rapid technology bring various influence culture foreigners who can influence attitudes and behavior generation young. Therefore that, internalization Pancasila values through education becomes very important for students capable maintain identity national, as well as build attitude morality, tolerance, and responsibility answer social. This research focus on the importance of implementation Pancasila values in system education for to form character a strong and integrated nation. With understand and practice Pancasila, it is hoped generation young can face challenges of the globalization era without lost teak self as Indonesian nation . Research results this can become guidelines for teachers, parents, and students policy in strengthen education character based on Pancasila in schools.